Friends forever : how girls and women forge lasting relationships - Degges-White, Suzanne (Rowman & Littlefield Publishers, 2011)
From their biological and cultural origins to the varied manifestations of social connections, this book explores the deep bonds forged between women. By sharing stories from girls and women throughout their lives, authors Degges-White and Gainey thoughtfully illustrate the roles that contemporary social relationships play at different stages in our lives while offering insights to deeper self-understanding and for finding, establishing, and sustaining relationships at any age.